Pengelolaan Sampah Berkelanjutan Sebagai Strategi Pendukung Pembangunan Berkelanjutan : Systematic Literature Review - Afif Nur Khayati; Amin Pujiati; Inaya Sari Melati (Yayasan Ekologi Masyarakat dan Sains, 2026)
Waste management is a major challenge faced by Indonesia, which ends up being related to environmental hunger and the achievement of sustainable development goals (SDGs). This study aims to identify sustainable management practices in Indonesia and broadcast how these strategies support sustainable development. The method used is the Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) approach. The results of the study indicate that various approaches such as waste bank programs, cross-sector collaboration, and community education and participation play an important role in realizing sustainable waste management. This study also highlights the importance of policy support, infrastructure, and innovation in waste management as an integral strategy to support sustainable development in Indonesia.